American literature - Secrest, Grace Anna (My University, 1896)
Introduction: Until the writers of the National period gave their writings to the public, American literature was at a low ebb, and there seemed little prospect of high attainment in the literary direction. The writers of the National period extending from 1830 to almost the present time may then be truthfully called the Founders of American literature. The down of our American literature is the time embraced between 1783 to 1860. It was then that literary demand took the place of other subjects that filled the minds of the people.
The founders of American literature
Citation: Secrest, Grace Anna. American literature. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: National period; American literature; Writer; Theses; Manuscripts (documents)